Frequency of sensitization to pollens of the subclass Rosidae in patients with respiratory allergy - Bedolla-Barajas, Martín; Valdez-López, Francisco; Arceo-Barba, Julieta; Bedolla-Pulido, Tonatiuh Ramses; Hernández-Colín, Dante; Morales-Romero, Jaime (Revista alergia Mexico (Tecamachalco, Pueblo, Mexico : 1993), 2014)
Studies related to the patterns of sensitization to rare species of aeroallergens are uncommon. To determine the frequency of sensitization to pollens clinically relevant in Allergology, corresponding to subclass Rosidae in patients with respiratory allergy. A cross-sectional study was done with patients included in a group with allergic rhinitis or asthma, respectively. We studied the clinical history, physical examination and reactivity to a panel of allergens, including the species Prosopis, Schinus, Acacia and Eucalyptus. Frequency of sensitization and confidence intervals at 95% (95%CI) were calculated. A total of 104 allergic rhinitis patients and 99 patients with asthma diagnosis were included. In both groups, the mean age corresponded to fourth decade of life. Women had greater frequency. In patients with allergic rhinitis, frequencies of sensitization were: mesquite tree 26.2% (95%CI: 17.7% to 34.6%), American pepper tree 11.5% (95%CI: 5.4% to 17.6%), eucalypt tree 6.7% (95%CI: 1.9% to 11.5%) and acacia tree 3% (95%CI: 0.3% to 6.3%). In subjects with asthma the results were as follows: mesquite tree 13.1% (95%CI: 6.5% to 19.7%), American pepper tree 7.1% (95%CI: 2% to 12.2%), eucalypt tree 4% (95%CI: 0.1% to 7.9%) and acacia tree 3% (95%CI: 0.4% to 6.4%). Both groups had a high frequency of sensitization to ash tree and oak tree followed by eucalypt, pine and acacia tree. Studied capacity of sensitization to tree pollens for this population is low, except for mesquite tree.